O estudo da natureza da luz : uma introdução à física quântica na 2ª série do Ensino Médio - Gama, Leonardo Pereira (2016)
We present a teaching unit (SD) (GUIMARÃES; GIORDAN, 2011) which aims the introduction of the Modern and Contemporary Physics in a concrete way to High School students through the study of the Nature of Light. In order to promote the implementation of a Physics teaching syllabus which includes the twentieth century science advances, it urgent to promote effective educational changes in the teaching method and in the teaching syllabus sequences. The purpose of this work is guided by a pedagogy inspired in Vygotsky's theory (2004, 2007, 2009), in which the teacher is a key part of both teaching and learning processes, most of the time acting as a skillful partner of the learners. Therefore, we have adopted the Study Situation steps (GEHLEN; MALDANER; DELIZOICOV, 2012) as a pedagogical practice. Our propose is to investigate the adoption of the corpuscular theory of light teaching in a second-year High School class through an SD applied to 31 private school students. As data collection instruments, it was used a questionnaire, audio recordings and video performance of activities, a computer simulation and low-cost experiments on the photoelectric effect, as well as a traditional evaluation. We describe the approach of the Optics study in fourteen textbooks approved by the National Textbook Plan (PNLD) for the year period from 2015 to 2017 in the review of literature. In addition, we report the study of several articles published in the past decade in selected journals related to the study of Light Nature by discussing the corpuscular and Undulating theories, and use of low cost and computational simulations experiments for teaching these theories. We conclude the viability of the study of the Nature of Light through the Photoelectric Effect teaching in second-year- High School classes. From there, we believe we should expand the practice to all High School Physics subjects, aiming a curriculum implementation which effectively enables the introduction of topics related to the early Twentieth Century discoveries, replacing the practice of teaching these topics only at the end of the course.